(untitled) (Dhaka University Journal of Science, 2015)
Electrical, optical and structural properties of p-type single crystal silicon were investigated in this work. Electrical conductivity of p-type silicon was measured in the temperature ranges 190 - 300 K. The acceptor ionization energy (?EA) was between 0.047 - 0.051 eV. Photoconductivity of the material was investigated by varying sample current, light intensity and temperature at a constant chopping frequency of 45.60 Hz. Absorption co-efficient (?) of the material was calculated from optical transmittance and reflectance measurements at room temperature (300 K) in the wavelength range of 300 -2500 nm. The direct optical band gap energy was found between 2.10 - 2.20 eV and the indirect optical band gap energy was found between 0.95 1.0 eV. The lattice parameter (a) was found to be 5.419Å from X-ray diffraction method (XRD). DOI: http://dx.doi.org/10.3329/dujs.v63i1.21766 Dhaka Univ. J. Sci. 63(1): 37-41, 2015 (January)